Residents’ perceptions of tourism and sustainable tourism management: planning to prevent future problems in destination management - The case of Cáceres, Spain - Raquel Caro-Carretero; Sandra Monroy-Rodríguez (Cogent Social Sciences)
This study explores residents’ opinions with the aim of understanding their perceptions of tourism in order to implement sustainable tourism practices in a medium-sized city such as Cáceres, which has been declared a UNESCO World Heritage Site (WHS), in order to mitigate negative impacts such as gentrification and tensions. Using principal component analysis (PCA) and cluster analysis these attitudes are studied and correlated with socio-demographic factors to enable effective planning of urban tourist accommodation. Residents recognize the benefits of tourism, such as economic growth and cultural preservation, but express concerns about the socio-economic and cultural impacts and emphasize the need to balance tourism growth with the needs of residents. The statistical analyses conducted reveal different attitudes towards tourism and highlight the importance of regulating and managing social and cultural impacts. The study argues for sustainable management strategies for tourism and proposes targeted measures to address community concerns and proactively prevent gentrification. By correlating perceptions with socio-demographic factors, it offers insights for the responsible integration of short-term rentals (VRUs) into urban areas.